Penerapan Quick Respon Code (Qr Code) Sebagai Alat Verifikasi Data Untuk Mencegah Kecurangan Pada Pembuatan Rekening Pdam Bumdes Di Desa Kiarapedes, Kabupaten Purwakarta Berbasis Web - rahmat, siska; ., Suherman; Ardiatma, Dodit (Prodi Sistem Informasi Universitas Dharma Andalas, 2023)
Water is an important part for the survival of all creatures. PDAM plays an important role in providing clean water and distributing it to the community. Kiarapdes Village, Purwakarta Regency has a Village-Owned Enterprise (BUMDES). PDAM has a significant role. However, decisive action is needed to ensure the efficient use of clean water. One of the efforts is to check water use through monthly reports and water meters. Obstacles arise due to delays in submitting water bills by officials which triggers the potential for fraud. The solution to overcome this problem is to implement a Web-based Quick Response Code (QR Code) Verification. The purpose of implementing a web-based QR Code as a Verification tool is to be an effective solution in preventing fraud in making PDAM Kiarapedes accounts, Purwakarta Regency. Web-based data verification system with the PDAM application name. This application system uses PHP and Python programming languages using Visual Code software and uses XAMPP and MySQL. The research method that the author uses is the Waterfall method because the work on a system is carried out sequentially. This system is expected to improve accuracy in making water accounts and reduce opportunities for fraud.